Predictors of Long-Term Exercise Capacity in Patients Who Have Had Lung Transplantation. (September 2018) - Mejia-Downs, Anne; DiPerna, Christen; Shank, Cori; Johnson, Rebecca; Rice, Danielle; Hage, Chadi
Introduction: Six-minute walk distance (6MWD) is a widely used surrogate for exercise capacity in patients both pre- and post-lung transplant. Multiple factors have been suggested to influence exercise capacity. Research Questions: This study sought to determine the change in exercise capacity over time and factors that influence long-term exercise capacity. Design: Data were collected prospectively on lung transplant recipients from 1 center. The 6MWD was measured preoperatively and at the 6- and 12-month clinic visits postoperatively. The Enright equation was used to calculate patients' percentage predicted 6MWD. The change in 6MWD over time was calculated, and multiple factors affecting 6MWD were analyzed, including predictors of 6MWD at 6 and 12 months posttransplant. Results: Sixty lung transplant recipients were enrolled. Significant improvement in 6MWD was found between pretransplant and hospital discharge and between hospital discharge and 6 months posttransplant. The percentage predicted 6MWD improved significantly from pretransplant to 6 months and to 12 months posttransplant. Factors associated with 6MWD were sex, diagnosis, graft type, and age. Factors predicting long-term exercise capacity included 6MWD at referral, pretransplant, and hospital discharge; pulmonary diagnosis; and type of transplant. Conclusion: The 6MWD provided useful information about patients' exercise capacity during phases of lung transplantation. The percentage predicted for each patient was found to be a more valuable measure than absolute 6MWD. Intensive, individualized training posttransplant is essential to optimize exercise capacity for this population